Adipose tissue function in the insulin-resistance syndrome. - Karpe, F; Tan, G (2005)
Insulin resistance is often seen as a consequence of obesity and there are several possible links between adipose tissue function and insulin resistance determined in other organs such as skeletal muscle or liver. One such link is the regulation of NEFA (non-esterified fatty acid) delivery to the rest of the body. Simplistically, an expanded adipose tissue mass delivers more NEFA to the systemic circulation and these fatty acids compete for substrate utilization in skeletal muscle, which in turn reduces glucose utilization. This increases blood glucose concentration and provides the stimulus for increased insulin secretion and hyperinsulinaemia is a key feature of the insulin-resistance syndrome. However, there is abundant evidence that adipose tissue is exquisitely insulin sensitive and hyperinsulinaemia may therefore lead to a constant lipolytic inhibition in adipose tissue. Consequently, the main function of adipose tissue, to rapidly switch between fat uptake and fat release, will be hampered. Adipose tissue blood flow is the conveyor of signals and substrates to and from the adipose tissue. In healthy people adipose tissue blood flow is much enhanced by food intake, whereas in insulin-resistant subjects this response is blunted. This is another facet of unresponsiveness of adipose tissue in the insulin-resistance syndrome.